PENYULUHAN DAN PENDAMPINGAN PENGOLAHAN KEARIFAN LOKAL IKAN BANDENG TARAKAN SEBAGAI UPAYA PENANGANAN STUNTING PADA BALITA - Nurul Hidayatun Jalilah; Agus Purnama Sari (Nindikayla Institute, 2023)
Community empowerment in communities affected by covid_19, especially housewives who have stunted toddlers provides its own color for business development that leads to the utilization of milkfish which is processed into various variants in line with the development of technological innovation in the culinary field of society. The methods used are outreach, training and mentoring, monitoring, and evaluation. The training participants were housewives from Gunung Lingkas Village, Tarakan City. The results achieved are that the processing of milkfish is a representative form of changing the paradigm of society in utilizing milkfish which has been processed traditionally with existing local ingredients, then switches to modern processing using modern technology to give the taste and tastes of service users who are passionate about Modern processed foods such as Milkfish Presto, Shredded Milkfish, Milkfish Sticks and Milkfish Crackers.